Discovery and Therapeutic Targeting of Differentiated Biofilm Subpopulations - Bisht, Karishma; Wakeman, Catherine Ann (Frontiers in Microbiology, 2019)
The association of microorganisms into biofilms produces functionally organized microbial structures that promote community survival in a wide range of environments. Much like when individual cells within a multicellular organism express different genes from the same DNA blueprint, individual microbial cells located within different regions of a biofilm structure can exhibit distinct genetic programs. These spatially-defined regions of physiologically-differentiated cells are reminiscent of the role of tissues in multicellular organisms, with specific subpopulations in the microbial community serving defined roles to promote the overall health of the biofilm. The functions of these subpopulations are quite diverse and can range from dormant cells that can withstand antibiotic onslaughts to cells actively producing extracellular polymeric substances providing integrity to the entire community. The purpose of this review is to discuss the diverse roles of subpopulations in the stability and function of clonal biofilms, the methods for studying these subpopulations, and the ways these subpopulations can potentially be exploited for therapeutic intervention.